Labor Force Activity after 60: Recent Trends in the Scandinavian Countries with Germany as a Benchmark - Mona Larsen; Peder J. Pedersen (Institute for the Study of Labor (IZA), 2015)
In most OECD member countries labor force attachment has increased in recent years in the 60+ group. Focus in the paper is on the development in this area in Denmark, Norway and Sweden since the 1990s. The development in the same period in the German labor market is included as a frame of reference. Main emphasis is given to the development in two distinct age groups, i.e. people in the first half of the 60s of which many are eligible for early retirement programs and people older than 65 mostly eligible for social security retirement programs. For these two age groups the actual development in labor force participation is described based on register data and on labor force surveys along with indicators of cohort relevant changes in education and health. Focus in the paper includes also the gender aspect to accommodate stronger cohort effects for women than for men. The impact on labor force participation from individual education and from self-assessed health is analyzed based on available micro data. Policy reforms and changes in the retirement area have been enacted since the mid-1990s in the included countries and more sweeping reforms are enacted or under review for the years ahead. We include a brief survey of policy changes in the Scandinavian countries and Germany as other determinants of labor force participation in the 60 and older group.
Keywords: I15; I25; J14; J26; 330; employment; older workers; health; education; program changes